Ames-2016 line lists for 13 isotopologues of CO2: Updates, consistency, and remaining issues. (December 2017) - Huang (黄新川), Xinchuan; Schwenke, David W.; Freedman, Richard S.; Lee, Timothy J.
Abstract: A new 626-based Ames-2 PES refinement and Ames-2016 line lists for 13 CO2 isotopologues are reported. A consistent σ RMS  = ±0.02 cm −1 is established for hundreds of isotopologue band origins using the Ames-2 PES. Ames-2016 line lists are computed at 296 K, 1000 K and 4000 K using the Ames-2 PES and the same DMS-N2 dipole surface used previously, with J up to 150, E ′ up to 24, 000 cm −1 or 18, 000 cm −1 and appropriate intensity cutoffs. The lists are compared to the CDSD-296, CDSD-4000 databases, UCL line lists, and a few recent highly accurate CO2 intensity measurements. Both agreements and discrepancies are discussed. Compared to the old Ames CO2 lists, the Ames-2016 line lists have line position deviations reduced by 50% or more, which consequently leads to more reliable intensities. The line shape parameters in the Ames-2016 line lists are predicted using the newly assigned conventional vibrational polyad quantum numbers for rovibrational levels below 12, 000 cm −1 so the quality of the line shape parameters is similar to that of CDSD or HITRAN. This study further proves that a semi-empirically refined PES (Ames-1 and Ames-2) coupled with a high quality ab initio DMS (DMS-N2 and UCL) may generate IR predictions with consistent accuracy and is thus helpful in the analysis of laboratory spectra and simulations of various isotopologues. The Ames-2016 lists based on DMS-N2 have reached the ∼1% intensity prediction accuracy level for the recent 626 30013-00001 and 20013-00001 bands, but further quantification and improvements require sub-percent or sub-half-percent accurate experimental intensities. The inter-isotopologue consistency of the intensity prediction accuracies should have reached better than 1–3% for regular bands not affected by resonances. Since the Effective Dipole Models (EDM) in CDSD and HITRAN have 1–20% or even larger uncertainties, we show that the Ames lists can provide better alternative IR data for many hard-to-determine isotopologue bands. Comparison at 4000 K suggests that the Ames-4000 K 12 C 16 O2 line list is reliable and consistent within the current cutoffs of J ≤ 150 and E ′  ≤ 24, 000 cm −1, but intensity contributions involving higher energy levels should not be omitted and future computations need to be converged up to at least 32, 000 cm −1 or higher. The remaining issues are discussed regarding the source of energy level discrepancies, intensity underestimations by ∼50% for some weak bands, etc. and also future work.